PENGARUH EKSTRAK ETANOL PROPOLIS TERHADAP EKSPRESI PROTEIN BCL2 DAN P21 DALAM MENEKAN PROLIFERASI DAN MENGINDUKSI APOPTOSIS PADA KULTUR SEL HEPATOMA (Hep G2) - Kun Salimah; Paulus Kusnanto; Bambang Purwanto (Biomedika, 2019)
Hepatocellular carcinoma (KHS) is 90% of primary tumors in the liver. One of natural treatment that have anti-cancer activity is propolis. Its anti-cancer activity works through induction of apoptosis and inhibition of cell proliferation. Bcl2 belongs to the family group B-cell lymphoma 2 protein which acts as an intrinsic pathway apoptotic protein. p21 is a tumor suppressor protein that has a primary function in inhibiting cell cycle progression. This study was aimed to determine the anti-cancer effect of propolis ethanol extract (EEP) originating from Kerjo, Karanganyar on hepatocellular cancer cell culture (Hep G2) through its potential as an anticancer in increasing p21 protein expression, reducing bcl2 protein expression in suppressing apoptosis and reducing cell proliferation . This research is an experimental laboratories with post test with control group design. Performed on Hep G2 cells with the treatment of EEP concentrations (½IC50, IC50, 2IC50), sorafenib IC50, a combination of EEP IC50 + sorafenib IC50, and controls. Observation of Bcl2 and p21 protein expression by immunocytochemistry method, observing cell proliferation with doubling time, observing apoptosis with flowcytometry. We use ANOVA statistical test, followed by the Tuckey post hoc test, were stated to be significant if p 0.05. The inhibition concentration of 50% Hep G2 cells by EEP was 65.2 μg / mL, and sorafenib (6.08 μg / mL). EEP concentration of 2IC50 (p = 0.001), sorafenib 1 IC50 (p = 0.001), 1IC50 EEP + 1IC50 sorafenib (p= 0.001) able to increase p21 protein expression. The 2 EEP concentration (p= 0.040), was able to reduce the expression of Bcl2 protein, with p= 0.001. The strength of EEP 1IC50 is equivalent to sorafenib IC50 in suppressing 24-hour proliferation (p 0.05). The strength of EEP ½IC50 is equivalent to sorafenib IC50 in suppressing proliferation 48 hours (p 0.05). The strength of EEP 1IC50 is better than sorafenib IC50 in suppressing proliferation of 72 hours (p 0.05). All EEP concentrations increase p21 protein expression, with the EEP 2IC50 group providing the strongest effect. All EEP concentrations were able to reduce cell proliferation, with the EEP 2IC50 group, giving the strongest effect. It was concluded that concentration of 2IC50 EEP has an effect on decreasing the expression of bcl2 protein and hepatoma cell apoptosis.Keywords: Ethanol Extract Propolis, Bcl2, P21, Apoptosis, Proliferation, Hep G2 Cells